ANALISIS KONVERGENSI PADA EMPAT KABUPATEN DI PULAU MADURA - Mohammad Rofik; Syaiful Anwar (J-ESA (Jurnal Ekonomi Syariah), 2019)
Development must have an impact on economic growth and economic growth must also have a real impact on the community, especially in revenue participation. This research aims to find out the pattern of economic growth and the inequality of income distribution in the four districts on Madura Island, based on the growth of Gross Regional Domestic Product (GRDP) in the four districts of the island of Madura. The data analysis technique used is calculating economic growth and convergence analysis with panel data regression data in four districts on Madura Island. The results showed that the economic growth patterns of the four districts of Madura island tended to experience flutuatition, while the calculation of Williamson index the level of disparity was still relatively low because it was below 0.5. Finally, the intensive analysis shows that the convergent value of 0.11 means that 4 districts in Madura have absolute convergence where underdeveloped regions can develop faster than developed regions